CRIMINAL PUNISHMENT AS AN EFFORT TO OVERCOME THE CRIMINAL ACT OF RECEIVING GOODS FROM THE PROCEEDS OF THE CRIME OF THEFT OF MOTOR VEHICLES - Santoso, Muhammad Iqbal; Hartanto; Wiryadi, Uyan (JILPR Journal Indonesia Law and Policy Review, 2025)
The most common criminal law in society is criminal acts against property (material crimes), such as theft, extortion, embezzlement, fraud, vandalism, and receiving. The existence of a receiver as a receiver for theft crimes makes it easy for the perpetrator to gain profit, so that the perpetrator of theft does not have to sell the stolen goods to consumers himself but can channel them through a receiver who pretends to be a trader. The problems that arise are both violations of social norms and legal regulations to create a phenomenon that is contrary to moral and ethical rules and legal regulations. In Article 480 of the Criminal Code concerning receiving goods, if understood from its elements, namely "required to know or should suspect that the goods received are the proceeds of crime" it is very confusing and difficult to distinguish if the goods received from the proceeds of crime were obtained in good ways and did not arouse any suspicion, such as buying and selling at a price that is generally appropriate, carried out in crowded and bright places and other ways that should not be suspected as crimes. (2) Recipients of goods resulting from crime who truly do not know and do not suspect that the goods they receive are the proceeds of crime for acceptable reasons as stated above can be considered consumers who must receive legal protection as regulated in Article 4 of Law Number 8 of 1999 concerning Consumer Protection.